Trajectories of Alcohol Use and Alcohol Intoxication in Young Adults Exposed to Childhood Violence and Later Problematic Drinking Behavior - Strøm, Ida Frugård (Journal of family violence, 2021)
This study examines the alcohol use and alcohol intoxication trajectories for victims of childhood violence over time and the potential pathways of relational difficulties and revictimization for the association between childhood abuse and problematic drinking behavior. The sample included 681 respondents (aged 19–37 years) from a follow-up study (2017) conducted via phone interviews derived from a community telephone survey collected in 2013. Individuals who were exposed to violence (n = 298) had higher starting levels of alcohol intoxication at age 16, but the controls (n = 383) had a steeper increase across time. The violence exposed cases reported more problematic drinking behavior than the controls. Significant predictors for problematic drinking behavior among the cases were revictimization (OR = 2.08, 95% CI:1.17–3.70), having deviant peer relationships (OR = 2.73, 95% CI:1.47–5.06) and low social support (OR 0.71, 95% CI:0.51–0.99). Clinicians need to be aware of the negative relationships between revictimization, social relationships and problematic drinking behavior in individuals exposed to childhood violence.